THE IMPORTANCE OF NON-STANDARD METHODS IN THE EFFECTIVE ORGANIZATION OF RUSSIAN LANGUAGE LESSONS - Madumarova Mukhayyo Djurayevna (Scholars Digest Publishing, 2025)
This article analyzes the importance of using non-standard methods in the effective organization of Russian language lessons. The possibilities of increasing students' speech activity, developing independent thinking and communicative competencies through innovative, interactive and creative approaches in the educational process are shown. The influence of non-standard methods on the effectiveness of teaching, the increased interest of students in the language and the focus on the practical application of acquired knowledge are also scientifically substantiated. The article also analyzes the current aspects of improving the professional skills of Russian language teachers and organizing the educational process in accordance with modern requirements.
Keywords: Russian language, innovation, training efficiency, non-standard methods, innovative approach, educational efficiency, creative thinking, communicative competence, interactive education, student activity.